STUDIES ON BEGONIA(BEGONIACEAE) OF THE MOLUCCA ISLANDS I: TWO NEW SPECIES FROM HALMAHERA, INDONESIA AND AN UPDATED DESCRIPTION OF BEGONIA HOLOSERICEA - Ardi, Wisnu H; Kusuma, Yayan W . C.; Lewis, Carl L.; Risna, Rosniati A.; Wiriadinata, Harry; Abdo, Melissa E.; Thomas, Daniel C. (Research Center for Biology, 2014)
Two new species of Begonia, Begonia holosericeoides Ardi & D. C. Thomas and B. aketajawensis Ardi & D. C. Thomas, are described from Aketajawe Lolobata National Park, Halmahera, Indonesia. The two species belong to Begonia section Petermannia. BegoniaÂ holosericea, previously only tentatively assigned to a section, is here assigned to section Petermannia based on the examination of newly available material. Additionally, a revised description and an illustration are provided. A key to the Moluccan species of Begonia is presented.